Un regard sur la notion de lésion de droits en matière de protection de la jeunesse - Ricard, Laurence (Les Cahiers de droit, 2021)
The notion of infringement of rights is the most sensitive issue in the practice of youth protection law. Paragraph 4 of section 91 of the Youth Protection Act provides that when the court seized of a child’s situation under the Act finds that a child’s rights have been infringed, it may order measures to correct the situation. When the rights of a child whose security or development is compromised, have possibly been infringed, the situation awakens the sensitivities of all of the parties involved and calls for diligent action. However, the court’s power to intervene in this matter is laconically defined in the piece of legislation. It has been the subject of unequal interpretations in case law without receiving particularly critical examination by the doctrine. The author therefore seeks to establish the basis for a rigorous legal understanding of this notion in order to render its interpretation consistent and recognize its limits.